Perceived stress and salivary cortisol on rock climbing - Madeira, Leonardo P.; Borghi, Filipy; Wilson, Vinicius D.; Souza, Aglecio L.; Pires-da-Rocha, Maria Cecilia; Ferreira, Heloisa A.; Grassi-Kassisse, Dora M.; Schwartz, Gisele M. [UNESP] (Wiley-Blackwell, 2019)
Rock climbing is a recreational activity that has been steadily growing in popularity over the years. The literature suggests that performers considered lead climbing was more stressful than other styles, but only few authors evaluated physical and mental stress was inherently associated with rock climbing. The aim of this study was to investigate the perceived stress and salivary cortisol release in rock climbers during two specific lead conditions: on-sight lead climb (OC) and flash lead climb (FC) in outdoors routes. Five intermediate male climbers (27.40 +/- 1.30 years) volunteered to attend anthropometric and body composition testing sessions. Psychological stress was measured by perceived stress questionnaire (PSQ), and salivary cortisol was collected at five times in rest (RD) and climbing days, before and after the protocols. PSQ score was 0.21 +/- 0.04 and they exhibited rhythmicity in daily cortisol production, which is most evidenced on RD with all values statistically different from upon awakening. No differences were observed when the days were compared by time point, total daily amount produced (AUC), or before and after the protocol. In conclusion, findings suggest that intermediate climbers appear to produce similar psychological or physiological responses during both climb style, but only on-sight exhibited an alteration in daily cortisol production.
Keywords: on-sight; rock climbing; salivary cortisol; stress